A disciplina de Didática no curso de Licenciatura em Matemática da UFPB/Campus IV na perspectiva dos estudantes - Rodrigues, Daniel (2022)
This research investigated the discipline of Didactics and its contributions to the training of teachers in the Mathematics Degree course at UFPB – Campus IV. The questions that guided this study were: what is the understanding formed about the discipline of Didactics for these students? What is the role attributed to the construction of pedagogical knowledge of mathematics teachers in training? From the methodological point of view, we used a qualitative approach and worked with a universe of 06 students of the Degree in Mathematics course at Campus IV of UFPB, working in Basic Education. With regard to data production procedures, we used document analysis and semi-structured individual interviews. The data show that the training of mathematics teachers needs a strong pedagogical bias and that Didactics is responsible for conducting this training. The results found allow us to say that the discipline of Didactics is approached from a critical, reflective and, mainly, political perspective. In addition, the undergraduates claim that Didactics helps in the construction of pedagogical practices and that the dis